Perception of coaches on decision making of novice basketball players - Jiménez, A. C. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2017)
Basketball is a team sport-opposition cooperation. Tactic is an important factor and is based on cognitive and motor components: perception, decision and performance. There are alternatives based on tactics to teach this sport. It is to start by understanding the game to achieve tactical and technical learning. The present study aims to determine the profile of basketball coaches in initiation on how raise the tactic, particularly the component of decision making in teaching. 89 coaches have participated, 72 male and 17 female. They have completed a questionnaire with 15 questions related to their personal data and on the use of tactical component in teaching basketball. The results show a majority of young coaches often encourage decision making and use exercises numerical superiority and equality.